2012
DOI: 10.2217/rme.12.32
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in Stem Cell Trials for Spinal Cord Injury: The Role of Networks and Peers

Abstract: The data suggest that novel strategies for decision-making processes, such as those involving peer support, are needed to enrich the knowledge base of all stakeholders. The results further underscore the importance of the role that both the academic and private sector play in ensuring the protection of human subjects in these trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…12,[14][15][16] Our results underscored the need to consider a patient's perception of risk as a dynamic rather than static phenomenon when designing clinical trials. Further research has interrogated the views of health-care professionals (HCPs) and injured individuals about the evidence needed to move from bench to bedside considering different risk frameworks.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…12,[14][15][16] Our results underscored the need to consider a patient's perception of risk as a dynamic rather than static phenomenon when designing clinical trials. Further research has interrogated the views of health-care professionals (HCPs) and injured individuals about the evidence needed to move from bench to bedside considering different risk frameworks.…”
Section: Introductionmentioning
confidence: 70%
“…9,12,[14][15][16] Definitions and meanings of risk vary, however, and understanding these in terms of hazard, exposure, consequence and probability is complex. 6 In this study, we identified three major differences in perspectives about risk between HCPs and ISCIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The legitimate involvement of other sources external to the health care system such as family, friends and the Internet can also complicate this already fragile landscape, 2,13 although the involvement of peers and other affected individuals may provide still untested benefits. 7 A summary of the balances and tensions is shown in Table 4. 17 this study and others highlight that the user go-to or information-pull strategy of existing resources is simply inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Trust and effective and trusted communication in the patient-physician relationship have been linked to positive patient behaviours involving treatment decisions, compliance and information disclosure. 5 In the present study, one of a series on readiness for clinical trials, 6 decision making, 7 expectation of benefit and risk, 8 advocacy 9 and risk, 10 we sought to examine how these trusting relationships specifically are fostered and threatened in the context of the conversation about stem cell interventions for SCI.…”
Section: Introductionmentioning
confidence: 99%